(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
The English competency of the Philippines is considered to be one of the greatest assets that made Filipinos known and recognized as a global workforce attracting foreign investors, which contributes to the growing economy of the country. English communication will always be the most useful skill of every educated Filipino because it is already embedded in our culture, history, and identity as a bilingual nation. However, a recent study states that the English competency of Filipinos declined in the past years. This research involved 30 Grade 11 students. A descriptive method was used, and a questionnaire was given to gather data from the respondents consisting of their profiles; the factors affecting English communication skills; and how the factors affect their daily conversational skills, written tasks, and public speaking skills. The majority of the respondents are females aged 17 years old from Humanities and Social Sciences Strand. The most significant factor was the medium of communication in which the practice of the language is observed daily. The respondents’ preference of which language to use as Filipinos are naturally bilingual. Therefore, the advantage and disadvantages of this situation significantly affect the fluency of students. Media influences the learners as they consume most of their time on social networking platforms, such as Facebook, where the proficiency of the English language is not given that much importance; slang and colloquialism have become the norm nowadays. Students are uncomfortable spoken English because of MTB, where primary learners are taught by using their MT thereby having difficulty in translating terms to English, which also leads to lacking ideas for creative writing. Communication becomes effective when a communicator is competent and has a broad understanding of the language. English competency provides a better opportunity in the corporate world and other fields. Family should help promote language development at home through a habitual study guided by parents. Curriculum developers should develop a curriculum that will meet the needs of diverse backgrounds and levels of English language learners and provide the most appropriate instructional material and approach for diverse learners to cope up with global competencies. A strong connection should be established between teachers and students to ease the learning process. Lastly, the use of social media should be maximized by creating an online platform that will serve as an extension of learning.